2022
DOI: 10.1038/s41557-022-01062-4
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable gating of non-equilibrium enzymatic feedback in chemically communicating polymersome nanoreactors

Abstract: The circadian rhythm generates out-of-equilibrium metabolite oscillations that are controlled by feedback loops under light/dark cycles. Here we describe a non-equilibrium nanosystem comprising a binary population of enzyme-containing polymersomes capable of light-gated chemical communication, controllable feedback and coupling to macroscopic oscillations. The populations consist of esterase-containing polymersomes functionalized with photo-responsive donor–acceptor Stenhouse adducts (DASA) and light-insensiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 57 publications
0
47
0
Order By: Relevance
“…Future work will focus on controlling the selectivity of fusion. Release of free energy could be used to overcome the entropic penalty that arises when fusion is targeted between two polymersome populations (i.e., crossed fusion). , The work presented here therefore lays the foundation for developing networks of out-of-equilibrium polymersomes capable of communicating via fundamental processes such as particle fusion. , It is clear that developing new mechanisms for temporally controlling the dynamics of polymersomes is essential to advance this area.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Future work will focus on controlling the selectivity of fusion. Release of free energy could be used to overcome the entropic penalty that arises when fusion is targeted between two polymersome populations (i.e., crossed fusion). , The work presented here therefore lays the foundation for developing networks of out-of-equilibrium polymersomes capable of communicating via fundamental processes such as particle fusion. , It is clear that developing new mechanisms for temporally controlling the dynamics of polymersomes is essential to advance this area.…”
Section: Discussionmentioning
confidence: 97%
“…104,105 The work presented here therefore lays the foundation for developing networks of out-of-equilibrium polymersomes capable of communicating via fundamental processes such as particle fusion. 106,107 It is clear that developing new mechanisms for temporally controlling the dynamics of polymersomes is essential to advance this area.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The evolution of compartmentalized environments on both cellular and subcellular levels (i.e., organelles) from protocells to modern cells allows various biological reactions to be processed selectively in confined spaces that simultaneously separate and protect them from detrimental external environments. Membrane structures are ubiquitous and compartmentalize various molecules into distinct microenvironments, performing numerous biological and life functions. , In this context, much effort has been devoted to the development of artificial nanoreactors to mimic these biological functions and processes in living systems. , In comparison with liposomes, polymersomes appear more suitable for the construction of nanoreactors due to their high structural stability, unique chemical versatility, facile functionalization, and tunable membrane permeability. …”
Section: Engineering Polymersomes As Smart Nanoreactorsmentioning
confidence: 99%
“…Despite DASA–polymer interactions being underexplored, the property changes associated with DASA photoswitching has led to the development of new light-responsive materials in the fields of targeted drug delivery, 35,48 wavelength-selective polymersome biocatalysis, 42,49 photolithography, 50 3D printing, 50,51 encryption, 52 surface wettability, 36,53 detection of toxic chemical warfare agents 54 and photothermal actuation. 37,38 While the types of materials into which DASAs have been incorporated are diverse, including inorganic nanoparticles 53,55 and as dopants in crosslinked polyurethane networks, 56 covalently-bound DASAs in crosslinked polymer networks have only recently been explored.…”
Section: Introductionmentioning
confidence: 99%
“…38,41,46 Studies by Sroda et al have also shown that the level of DASA functionalisation itself affects T g and elastic modulus of the host polymer, 38 while Yap et al demonstrated polymer chain-length dependence on DASA switching performance, with shorter chains (of ∼20 monomer units) showing faster switching compared to longer chainlengths (of ∼100 monomer units). 43 Despite DASA-polymer interactions being underexplored, the property changes associated with DASA photoswitching has led to the development of new light-responsive materials in the fields of targeted drug delivery, 35,48 wavelength-selective polymersome biocatalysis, 42,49 photolithography, 50 3D printing, 50,51 encryption, 52 surface wettability, 36,53 detection of toxic chemical warfare agents 54 and photothermal actuation. 37,38 While the types of materials into which DASAs have been incorporated are diverse, including inorganic nanoparticles 53,55 and as dopants in crosslinked polyurethane networks, 56 covalently-bound DASAs in crosslinked polymer networks have only recently been explored.…”
Section: Introductionmentioning
confidence: 99%